Combined application of vermicompost and mineral K fertilizer improves root yield of sweet potato [Ipomoea batatas (L.) Lam] in Southern Ethiopia - Alemu Degwale; Geletaw Kebede; Ashenafi Woldeselassie; Fanuel Laekemariam (Heliyon)
The high cost of mineral fertilizers, lack of credit, and delivery delays constrain crop production in the developing world like Ethiopia. Farmers apply little or no fertilizer to sweet potatoes leading to lower root yield (8 t ha−1) compared with 60 t ha−1 in research fields. Eventually, this has led to a decline in food security. Although the rate depends on many factors, organic inputs such as vermicomposts are suggested as alternatives or combined with mineral fertilizers. This research was therefore initiated to investigate the effect of the combined application of vermicompost (VC) and mineral K fertilizer on the root yield of sweet potatoes. Treatments were 0, 4, 8, or 12 t ha−1 VC and 0, 50, 100, or 150 kg ha−1 K laid out in a Randomized Complete Block Design, factorial arrangement with three replications. The combined application of 12 t VC ha−1 with 150 kg K ha−1 produced the highest total root yield (57.35 t ha−1), marketable root yield (46.45 t ha−1), and harvest index (16.5 %). These values were comparable to those of 8 t VC ha−1 and 150 kg K ha−1. Dry matter content was increased by 35.5 % in location-1 and 38.2 % in location-2 at combined rates of 12 t VC ha−1 and 150 kg K ha−1 that did not differ from 8 t VC ha−1 and 150 kg K ha−1. Root diameter, dry matter content, harvest index, marketable, and total root yield had a strong positive relationship. Applying 8 t VC ha−1 with 150 kg K can improve root yield aboveground biomass of sweet potato.